Estimation of discount rates in Latin America: empirical evidence and challenges - Fuenzalida, Darcy (2010)
This paper compares the main proposals that have been made in order to estimate discount rates in emerging markets. Seven methods are used to estimate the cost of equity capital in the case of global well-diversified investors; two methods are used to estimate it in the case of imperfectly diversified local institutional investors; and one method is used to estimate the required return in the case of non-diversified entrepreneurs. Using the first nine methods one estimates the costs of equity for all economic sectors in six Latin American emerging markets. Consistently with studies applied to other regions a great deal of disparity is observed between the discount rates obtained across the different models which implies that no model is better than the others. Likewise the paper shows that Latin American markets are in a process of becoming more integrated with the world market because discount rates have decreased consistently during the first five-year period of the XXI Century. Finally on identifies several challenges that have to be tackled to estimate discount rates and valuate investment opportunities in emerging markets.